Efektivitas Sanksi Pidana terhadap Pelaku Pencurian dengan Pemberatan dalam Perspektif Hukum Pidana Nasional - Handione, Denaloy Valentino; Permana, Yana Sukma (LPPM Iblam School of Law, 2024)
The effectiveness of criminal sanctions against perpetrators of aggravated theft remains a crucial issue in Indonesia’s criminal justice system. Despite clear legal regulations, disparities in sentencing and law enforcement practices continue to hinder the deterrent effect of these sanctions. Social and economic factors also play a significant role in influencing crime rates, making it essential to evaluate the actual impact of existing laws. This study examines the effectiveness of criminal sanctions for aggravated theft within the framework of national criminal law.This research employs a qualitative method with a normative juridical approach, focusing on legal regulation analysis and judicial interpretation. Data collection was conducted through an extensive literature review, utilizing both primary legal sources and secondary references.The findings reveal that sentencing inconsistencies and weak law enforcement contribute to the limited effectiveness of criminal sanctions. In contrast, comparative studies with other legal systems show that restorative justice approaches can reduce recidivism and enhance victim satisfaction. Although Indonesian law recognizes such concepts, their implementation remains constrained by legal and institutional barriers. Therefore, a more comprehensive legal reform is required to balance punitive measures with rehabilitative strategies